IMPLEMENTASI PENDEKATAN OPPORTUNITY SOLUTION TREE DAN FISHBONE ANALYSIS DALAM PENGUATAN MANAJEMEN RISIKO RUMAH SAKIT: STUDI KUALITATIF DI RSU MUHAMMADIYAH METRO - Maya Aprilianingisih; Rizky Aprilianti Lestari; Windi Peritiwi; Yogi Catur Putra; Nurbaiti (Journal of Hospital Administration and Excellent Health Service, 2026)
Risk management is an important component in ensuring the quality of service and patient safety in hospitals. The implementation of risk management, which is still reactive, causes various potential risks not to be identified and mitigated optimally. This study aims to explore the implementation of the Opportunity Solution Tree (OST) and Fishbone Analysis approaches in strengthening risk management at RSU Muhammadiyah Metro. The research uses a qualitative approach with a case study design. Informants were selected through purposive sampling, consisting of directors, department heads, managers, assistant managers, quality team leaders, and unit heads involved in hospital risk management. Data collection was carried out through in-depth interviews, observation, Focus Group Discussions (FGD), and document review. Data analysis used the interactive model of Miles, Huberman, and Saldaña through the stages of data reduction, data presentation, and drawing conclusions. The research results show four main themes: increased management awareness of the importance of proactive risk management, ease of identifying root causes through Fishbone Analysis, OST's ability to develop more structured alternative solutions, and implementation obstacles such as limited HR competencies, a reporting culture that is not yet optimal, and the lack of integration in the risk management information system. The implementation of OST and Fishbone Analysis is considered capable of improving cross-unit collaboration in the process of risk identification and mitigation. This study concludes that applying OST and Fishbone Analysis contributes positively to strengthening risk management at RSU Muhammadiyah Metro and supports shifting the risk management paradigm from reactive to proactive.